The Philippine islands, 1493-1803 explorations by early navigators, descriptions of the islands and their peoples, their history and records of the Catholic missions, as related in contemporaneous books and manuscripts, showing the political, economic, commercial and religious conditions of those islands from their earliest relations with European nations to the beginning of the nineteenth century, Volume III, 1569-1576 - Blair, Emma Helen 1911; Robertson, James Alexander 1873-1939; Bourne, Edward Gaylord 1860-1908
The documents presented in this volume cover the last three years of Legazpi's administration in the islands, the governorship of Guido de Lavezaris, and the beginning of that of Francisco de Sande. In the brief period which we thus far survey, the first decade of Spanish occupation (1565-75), are already disclosed the main elements of the oriental problem of today: the conflicting claims of powerful European nations, striving for advantage and monopoly in the rich trade of the East; the'eagerness of unscrupulous Europeans to subjugate the wealthy but comparatively defenseless Chinese people, and the efforts of the latter to exclude foreigners from their country; the relations between the dominant whites and the weaker colored races; the characteristics, racial and local, of the various oriental peoples ; the Chinese migration to the islands; and the influence of the missionaries. Interesting comparisons may be made between the conquests by the Spaniards in the Philippines and those made at an earlier period in New Spain.